Osmotic core-shell polymeric implant for sustained BDNF AntagoNAT delivery in CNS using minimally invasive nasal depot (MIND) approach. (September 2021) - Padmakumar, Smrithi; Jones, Gregory; Khorkova, Olga; Hsiao, Jane; Kim, Jonghan; Bleier, Benjamin S.; Amiji, Mansoor M.
Abstract: The development of drug delivery strategies for efficacious therapeutic administration directly into the central nervous system (CNS) in a minimally invasive manner remains a major obstacle hindering the clinical translation of biological disease-modifying therapeutics. A novel direct trans -nasal delivery method, termed 'Minimally-Invasive Nasal Depot' (MIND), has proved to be successful in providing high CNS uptake and brain distribution of blood-brain barrier (BBB) impermeant therapeutics via direct administration to the olfactory submucosal space in a rodent model. The present study describes the engineering of custom-made implants with a unique architecture of an "osmotically-active core" entrapping the therapeutic and a "biodegradable polymeric shell" to enable long-acting delivery using the MIND procedure. The MIND-administered implant provided sustained CNS delivery of brain derived neurotrophic factor (BDNF) AntagoNATs for up to 4 weeks in Sprague Dawley rats resulting in significant endogenous BDNF protein upregulation in several brain tissues. The biocompatibility of such core-shell implants coupled with their substantial pharmacokinetic advantages and safety of the MIND procedure highlights the practical utility and translational potential of this synergistic approach for treatment of chronic age-related neurodegenerative diseases. Graphical abstract: Image 1